Die Innenstadt von Babylon (Merkes) - Reuther, Oscar (1968)
Mit 120 Abb. im Text u. 95 Taf. Neudr. d. Ausg. 1926 (Osnabrück, Zeller); Getr. Pag. (286 S, 95 Bl. Abb u. Ktn) 4; Ausgrabungen der Deutschen Orientgesellschaft in Babylon, 3; Lw. 490. M. –.